Maturity indices for tomato (Solanum lycopersicum L.), cv. Ghalia 281 in Central Uganda - Okiror, Paul; Lejju, Julius Bunny; Bahati, Joseph; Kagoro Rugunda, Grace; Sebuuwufu, Collins Inno (African Journal of Agricultural Research, 2017)
Application of maturity indices and optimal harvest time improves handling and marketing operations and minimizes pre and postharvest losses for tomato products. Growth patterns of tomato (Solanum lycopersicum L.), cv. Ghalia 281, were therefore analyzed to determine nondestructive maturity indices for optimal harvest regimes. Propagation experiments were run in central Uganda in 2015. A total of 216 tomato fruits were tagged and their diameter, height and color recorded daily prior to physico-chemical and nutritional analyses at Makerere University Food Science and Technology laboratory. The longest fruit (5.55 cm) was from breaker, while the shortest (4.95 cm) was in light red samples. Total soluble solids were highest at breaker (5.40 °Brix) and red (6.00 °Brix) and was lowest at turning stage (4.00 °Brix). Green tomatoes had the highest carbohydrate content of 5.99 g/100 g, followed by breaker tomatoes with 5.71 g/100 g, while the lowest CHO (4.17 g/100 g) was observed from tomatoes at turning stage. The pH decreased from 4.98 (green) to 4.60 (light red). Protein content was highest (13.05%) from red tomatoes and lowest in pink samples (10.22%). Fruit diameter was negatively correlated with fruit color (r = -0.748, P≤0.05) and °Brix (r = -0.787, P≤0.05). A highly negative correlation occurred between fruit age and pH (r = -0.949, P≤0.05). There was a high positive correlation between fruit diameter and total titrable acidity (r = 0.959, P≤0.05). Optimal harvesting should occur at breaker for distant markets and fruit with red outer colour be proposed for local consumers. Maturity indices for determining harvest time of tomato is a combination of fruit age, diameter and color, because these correlate significantly with physico-chemical and nutritional characteristics including total soluble solids (TSS), total titrable acidity (TTA) and protein content.
Keywords: Color; Fruit diameter; Maturity index; Solanum lycopersicum; Total soluble solids; Vegetables